2022
DOI: 10.3389/fphys.2022.996020
|View full text |Cite
|
Sign up to set email alerts
|

An electron microscopic and biochemical study of the potential protective effect of ginger against Cadmium-induced testicular pathology in rats

Abstract: Background: Cadmium (Cd) is a toxic heavy metal used in many industries. Since the second half of the 20th century, legislation on Cd use was put to limit the exponential rise in its environmental levels. This study aimed to investigate Cd’s functional and ultrastructural changes on rats’ reproductive systems and the role of Zingiber officinale (Ginger) in protecting against Cd-induced toxicity.Methods: Thirty adult male albino rats were randomly assigned into three equal groups (n = 10); control, Cd-exposed/u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…They found that ginger (250 mg/kg), particularly when combined with zinc, can mitigate reproductive dysfunction by inhibiting apoptosis through the lowering of oxidative damage and inflammation, thus leading to enhanced reproductive performance. Moreover, Motawee et al (2022) [140] investigated the potential protective effect of ginger root powder against Cd-induced testicular pathology in rats. Their data suggested that ginger (40 mg/kg/day) exerted a protective effect against the deterioration of testicular tissue structure and function induced by Cd.…”
Section: Ginger (Zingiber Officinale)mentioning
confidence: 99%
“…They found that ginger (250 mg/kg), particularly when combined with zinc, can mitigate reproductive dysfunction by inhibiting apoptosis through the lowering of oxidative damage and inflammation, thus leading to enhanced reproductive performance. Moreover, Motawee et al (2022) [140] investigated the potential protective effect of ginger root powder against Cd-induced testicular pathology in rats. Their data suggested that ginger (40 mg/kg/day) exerted a protective effect against the deterioration of testicular tissue structure and function induced by Cd.…”
Section: Ginger (Zingiber Officinale)mentioning
confidence: 99%